#TITLE_ALTERNATIVE# - TAUFIK A. S. (NIM 10204021), FIKI
The Ricci flow, which connects metric evolution and curvature of space, was introduced by Richard Hamilton in 1981 in order to gain insight into the geometrization conjecture of William Thurston, concerning the topological classification of threedimensional smooth manifold. Many physicist believed that Ricci flow related to physical phenomena, especially gravity. In this project, we will derive an exact solution of Ricci flow equation for axisymmetric metric in 4D for static condition (! = 0), and using assumption that all the function that forming the metrics are integrable.